2011
DOI: 10.1088/0953-8984/23/49/495401
|View full text |Cite
|
Sign up to set email alerts
|

Structural, elastic, vibrational and electronic properties of amorphous Al2O3fromab initiocalculations

Abstract: First-principles molecular dynamics calculations of the structural, elastic, vibrational and electronic properties of amorphous Al(2)O(3), in a system consisting of a supercell of 80 atoms, are reported. A detailed analysis of the interatomic correlations allows us to conclude that the short-range order is mainly composed of AlO(4) tetrahedra, but, in contrast with previous results, also an important number of AlO(6) octahedra and AlO(5) units are present. The vibrational density of states presents two frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 41 publications
5
43
0
Order By: Relevance
“…The result from EPSR for sample 2 using this density gives an average Al-O coordination number of 4.62, which is close to the value for glassy alumina from our classical MD simulation (density of 3.21 g cm −3 ). Our MD simulation result at 300 K is expected to provide an indication of how an alumina glass structure (could it be made) might look, with 49.5% AlO 4 , 42.0% AlO 5 , and 8.5% AlO 6 units ( Table 3), which is consistent with the results of ab initio MD simulation reported by Davis and Gutiérrez (2011). Also, both EPSR and MD simulation results of this work are similar to those measured by 27 Al NMR for amorphous alumina made by sputtering techniques (Lee et al, 2009(Lee et al, , 2010Lee and Ryu, 2017).…”
Section: Coordination Number Distributionssupporting
confidence: 89%
“…The result from EPSR for sample 2 using this density gives an average Al-O coordination number of 4.62, which is close to the value for glassy alumina from our classical MD simulation (density of 3.21 g cm −3 ). Our MD simulation result at 300 K is expected to provide an indication of how an alumina glass structure (could it be made) might look, with 49.5% AlO 4 , 42.0% AlO 5 , and 8.5% AlO 6 units ( Table 3), which is consistent with the results of ab initio MD simulation reported by Davis and Gutiérrez (2011). Also, both EPSR and MD simulation results of this work are similar to those measured by 27 Al NMR for amorphous alumina made by sputtering techniques (Lee et al, 2009(Lee et al, , 2010Lee and Ryu, 2017).…”
Section: Coordination Number Distributionssupporting
confidence: 89%
“…a‐Al 2 O 3 has about three times larger modulus than SLSG if we apply the Pedone's interatomic potential. The estimated elastic properties of a‐Al 2 O 3 are definitely smaller than those evaluated by ab‐initio MD simulation (Young's modulus ( E y ) is 340.3 GPa, shear modulus ( G ) is 141.0 GPa), whereas the calculated E y is larger than experimentally measured one on amorphous anodic aluminum film (122 ± 12 GPa). Unfortunately, to the best of our knowledge, there is no experimental data of mechanical properties of bulk amorphous aluminum.…”
Section: Simulation Resultsmentioning
confidence: 58%
“…Firstly, we showed that when comparing to DFT results, the most complex potentials naming Streitz's, Vashishta's and Woodley's potentials are not able to recover DFT results on the smallest alumina molecules (Al 2 O 3 ) n with n ≤ 8. In contrast, the Alvarez's potential shows a remarkable agreement with DFT results and can be therefore employed as a starting optimization tool before DFT calculations 47,53,64 . Secondly, the amorphous to crystal transition occurring at intermediate sizes was found for all the potentials.…”
Section: Discussionmentioning
confidence: 85%